When drought meets forest management: Effects on the soil microbial community of a Holm oak forest ecosystem - Bastida, F; López-Mondéjar, R; Baldrian, P; Andrés-Abellán, M; Jehmlich, N; Torres, I F; García, C; López-Serrano, F R (The Science of the total environment, 2019)
The growth and survival of plants in semiarid Mediterranean forests can be improved through the benefits conferred by thinning, a forest management practice that removes trees and reduces the competition between the remaining ones. Here, we evaluate the impacts of induced drought (the exclusion of 25% of the natural rainfall for 5 years) and thinning, and their interaction, with the objective of determining whether the thinning of Holm oak (Quercus ilex L.) modulates the resistance of the soil microbial community to drought. Sequencing of 16S rRNA and ITS amplicons revealed that drought, thinning, and their interaction influenced the composition of the bacterial community, while the fungal community was exclusively affected by thinning. Thinning consisted of the removal of the aboveground parts of the Holm oak trees, which were thereafter left in forest stand. Thinning contributed to the C and N contents, with parallel increases in microbial biomass, particularly in summer. Drought increased the amounts of total organic C and total N, likely due to the reduced enzyme activities. Indeed, the composition of the bacterial community was modulated primarily by the indirect and long-term effects of drought - the accumulation of soil organic matter - rather than by the direct effect of the lower water content imposed by the drought treatments. Thinning under drought conditions did not increase soil organic C (SOC) content. However, the resistance of the soil microbial community to drought was fostered by thinning, particularly at the functional level, as indicated by the enzyme activities related to C, N and P cycles. These responses were associated to variations in the composition of the microbial communities in thinned, drought-exposed plots, in comparison to unthinned, drought-exposed plots. In conclusion, the interaction between forest management and drought influenced the soil microbial community of a Holm oak-dominated Mediterranean ecosystem.
Keywords: biomasa; Fungi; Semiarid; Climate Change; Quercus; Spain; Biomass; Thinning; Forests; mikrobiota; Droughts; Bacteria; houby; Soil Microbiology; lesnictví; Microbiota; Holm oak; Enzyme activity; Drought; Soil microbial community; Španělsko; klimatické změny; Forestry; dub (rod); půdní mikrobiologie; lesy; období sucha